COLLABORATIVE GOVERNANCE DALAM PENANGGULANGAN BENCANA BANJIR DI LINGKUNGAN LEBAK KELURAHAN TUKANGKAYU KABUPATEN BANYUWANGI - Sulthon Rohmadin; Dea Apsari Pramudana Putri; Yusi Eva Batubara (Jurnal Konstituen, 2025)
The Lebak neighborhood is a residential area in Banyuwangi Regency which is always hit by annual floods. The densely populated condition of the area and the lack of public awareness about not throwing rubbish into the river is a challenge in itself. For this reason, collaboration between related parties is needed to run the flood disaster management process well. This research aims to find out, analyze, and describe how Collaborative Governance is implemented between the government, the business world, and community groups in the Lebak Environment, Tukangkayu Village, Banyuwangi District, Banyuwangi Regency in managing flood disasters. This research uses a qualitative descriptive method using primary and secondary data sources. This research relies on data collection techniques through interviews, observation, and documentation to obtain the required data. The research results show that collaboration between the government, the business world, and community groups has been implemented but is not yet optimal, so maximizing the role at the preventive and monitoring stages is necessary. The government still tends to be more dominant than the business world and community groups. This collaborative process resulted in two permanent water pumping machines, river cleaning, a river normalization program, and the implementation of a disaster task force consisting of all stakeholders. In implementing this collaboration, there are several obstacles, such as a lack of public awareness of the importance of not throwing rubbish or waste into the river, difficulty in accessing heavy equipment in the form of excavators to the river, problems with the operation of water pump machines, the conversion of plantation crop commodities in upstream areas, and the very low condition of the Lebak area. Based on the problems faced, efforts are needed to maximize the role of each party involved at each stage of disaster management as well as innovation related to solving the problems being experienced. Keywords: Flood, Collaborative Governance, Disaster Management